Hardening Azure Applications - Gaurav, Suraj; Machiraju, Suren (Apress : Imprint: Apress, 2015)
Learn what it takes to build large scale, mission critical applications -hardened applications- on the Azure cloud platform. This 208 page book covers the techniques and engineering principles that every architect and developer needs to know to harden their Azure/.NET applications to ensure maximum reliability and high availability when deployed at scale. While the techniques are implemented in .NET and optimized for Azure, the principles here will also be valuable for users of other cloud-based development platforms. Applications come in a variety of forms, from simple apps that can be built and deployed in hours to mega-scale apps that need significantly higher engineering rigor and robust organizations to deliver them. How do you build such massively scalable applications to keep pace with traffic demands while always being 'online' with five 9's availability? The authors take you step by step through the process of evaluating and building applications with the appropriate hardness attributes. For example, it is easy to say that an application should be available "all the time", but it is very important to understand what each level of 9 for availability means and the resulting implications on engineering and resources. The book explains the details required for developers and IT Pros to get it right in Azure.